KEPASTIAN HUKUM KEBIJAKAN NASIONAL DALAM PENGEMBANGAN KOMPETENSI BAGI PEGAWAI NEGERI SIPIL MELALUI JALUR PENDIDIKAN - Herdia Noor Hafnita; Hedwig Adianto Mau; Mardi Candra (Journal of Innovation Research and Knowledge, 2025)
Proffesionalism is one of the key factors in the success of civil servants (PNS) in implementing public policies, providing services to the community, and fostering unity in national life. Professionalism reflects a person's attitude and competence in a specific field when performing their duties. A civil servant's professionalism can be developed through various means, one of which is education, either through funded study assignments or self-financed study programs. In carrying out study assignments, national regulations are needed to provide legal guidelines for their implementation. These include requirements for study assignments, their execution, the rights and obligations of employees undertaking them, as well as monitoring and evaluation of the process. Currently, regulations related to study assignments for civil servants refer to Presidential Regulation Number 12 of 1961 and the Prime Minister's Decree Number 224/MP/1961. However, these regulations are no longer relevant to current conditions, and many aspects of employee competency development require updated provisions. Therefore, it is necessary to establish new national regulations to revise or replace Presidential Regulation Number 12 of 1961 and the Prime Minister's Decree Number 224/MP/1961.The research method used is normative juridical with a statute approach, conceptual approach, analytical approach, and case approach, utilizing Gustav Radbruch's theory of legal certainty and competency theory.The research results indicate that the current national policy on civil servant competency development through education, as stipulated in Presidential Regulation Number 12 of 1961 and the Prime Minister's Decree Number 224/MP/1961, is no longer relevant or aligned with current developments. Additionally, the circular issued by the Ministry of State Apparatus Utilization, which serves as a guideline for competency development, lacks legal force. Therefore, a regulation governing the competency development of civil servants through education is necessary to align with existing laws and regulations, ensuring legal certainty in its implementation.